Strategic Adaptation of Students and Lecturers to Face an Independent Campus - Salabi, Ahmad; Sarkati, Ahmad; Gurhan, Ethem; Sholeh, Makherus (Al-Hayat: Journal of Islamic Education, 2025)
This study aims to evaluate the readiness of lecturers and students in the Islamic Education Management (IEM) Study Program at UIN Antasari Banjarmasin in facing the Independent Campus policy in the era of the Industrial Revolution 4.0. Using a mixed method, this research involved 83 informants, consisting of 70 students and 13 lecturers. Data were collected through in-depth interviews, surveys, observations, and documentation. The data analysis process involved data reduction and verification techniques to ensure the accuracy of the findings. The results showed that highlighting the readiness of lecturers and students physically and in terms of knowledge. Innovation and improvisation through 1) Adjusting the curriculum by adopting the MBKM curriculum and making gradual changes to the learning system for the IEM program; 2) Establishing cooperation with partner schools and IEM study programs at other campuses in Indonesia; 3) Increasing the capacity of IEM lecturers to respond to technological advancements and integrate them into lectures through seminars, workshops, research, and mentoring; 4) Conducting more innovative and creative IEM program activities, both academic and non-academic, in collaboration with the IEM Department Student Association (DSA). Although several efforts have been made, there are still significant obstacles. These include inadequate facilities, budget constraints, and low motivation and innovation among lecturers and students. This research concludes that further support from the university, as well as improvements to infrastructure and resources, are essential to support the successful implementation of the Merdeka Campus policy and improve graduates' readiness to face the Industrial Revolution 4.0.